Glycogen synthase kinase 3ß participates in late stages of Dengue virus-2 infection (2020)
ABSTRACT: Background: Viruses can modulate intracellular signalling pathways to complete their infectious cycle. Among these, the PI3K/Akt pathway allows prolonged survival of infected cells that favours viral replication. GSK3β, a protein kinase downstream of PI3K/Akt, gets inactivated upon activation of the PI3K/Akt pathway, and its association with viral infections has been recently established. In this study, the role of GSK3β during Dengue virus-2 (DENV-2) infection was investigated. Methods: GSK3β participation in the DENV-2 replication process was evaluated with pharmacological and genetic inhibition during early [0-12 h post-infection (hpi)], late (12-24 hpi), and 24 hpi in Huh7 and Vero cells. We assessed the viral and cellular processes by calculating the viral titre in the supernatants, In-Cell Western, western blotting and fluorescence microscopy. Results: Phosphorylation of GSK3β-Ser9 was observed at the early stages of infection; neither did treatment with small molecule inhibitors nor pre-treatment prior to viral infection of GSK3β reduce viral titres of the supernatant at these time points. However, a decrease in viral titres was observed in cells infected and treated with the inhibitors much later during viral infection. Consistently, the infected cells at this stage displayed plasma membrane damage. Nonetheless, these effects were not elicited with the use of genetic inhibitors of GSK3β. Conclusions: The results suggest that GSK3β participates at the late stages of the DENV replication cycle, where viral activation may promote apoptosis and release of viral particles.